Optical bandgap widening and phase transformation of nitrogen doped cupric oxide - Masudy-Panah, Saeid (2016)
The structural and optical properties of sputter deposited nitrogen (N) doped CuO (CuO(N)) thin films are systematically investigated. It is found that the incorporation of N into CuO causes an enlargement of optical bandgap and reduction in resistivity of the CuO(N) films. Furthermore, a gradual phase transformation from CuO to Cu2O is observed with the increase in N concentration. The effects of annealing temperature on the structural properties of CuO (N) and its dependence on N concentration are also investigated. It is observed that the phase transformation process from CuO to Cu2O significantly depends on the N concentration and the annealing temperature. Heterojunction solar cells of p-type CuO(N) on n-type silicon (Si) substrate, p-CuO(N)/n-Si, are fabricated to investigate the impact of N doping on its photovoltaic properties.